2014
DOI: 10.1016/j.ajpath.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Nestin Delineates Pancreatic Cancer Stem Cells in Metastatic Foci of NOD/Shi-scid IL2Rγnull (NOG) Mice

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is associated with a high incidence of hepatic metastases, as well as occasional pulmonary metastases. To delineate the potential role of cancer stem cells (CSCs) in PDAC metastasis, human PDAC cells were injected into the spleen of mice. The characteristics and expression of markers associated with CSC and epithelial-mesenchymal transition (EMT) of metastatic cells that developed in the liver and lung were then compared with parental cells. The metastatic cells were pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 22 publications
3
60
0
1
Order By: Relevance
“…Our previous studies have shown that nestin regulates the sphere formation ability of glioblastomas, melanomas, lung adenocarcinomas, and pancreatic cancer [23][24][25]. In this study, nestin was detected in perivascular and perinecrostic lesions, which are considered a niche for BTSCs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our previous studies have shown that nestin regulates the sphere formation ability of glioblastomas, melanomas, lung adenocarcinomas, and pancreatic cancer [23][24][25]. In this study, nestin was detected in perivascular and perinecrostic lesions, which are considered a niche for BTSCs.…”
Section: Discussionmentioning
confidence: 53%
“…We have also shown that knockdown of nestin expression suppresses migration, invasion, and sphere formation in pancreatic cancer [22,23], malignant melanomas [24] and lung cancer [25]. Similarly, Lu et al demonstrated that blocking the expression of nestin in glioblastomas by intratumoral injection of shRNA significantly reduced tumor growth and volume [19].…”
Section: Introductionmentioning
confidence: 89%
“…In a previous study, we reported that nestin, a pancreatic CSC marker, is more highly expressed in the spheres of three PDAC cell lines than in nonsphere cells (13). Moreover, pancreatic cancer cells derived from metastatic foci of immunodeficient mice form a greater number of spheres in low-attachment plates than do their primary tumor counterparts (14). These findings suggest that CSCs are enriched in the spheres and play an important role in the aggressiveness of PDAC.…”
Section: Introductionmentioning
confidence: 80%
“…17 After 5 days of culture, the number of spheres in each well was counted. Total RNA was extracted from spherical cells and nonspherical cells and was used for PCR analysis.…”
Section: Sphere Formation Assaymentioning
confidence: 99%
“…16,17 Immunoblotting was performed using an anti-nestin antibody (diluted 1:2,000; BD Bioscience, Franklin Lakes, NJ).…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%